Mortality from multiple sclerosis and exposure to residential and occupational solar radiation: a case-control study based on death certificates. Issue 6 (1st June 2000) - Freedman, D Michal; Dosemeci, Mustafa; Alavanja, Michael C R
Abstract : OBJECTIVES: To explore whether mortality from multiple sclerosis is negatively associated with exposure to sunlight. METHODS: Two case-control studies based on death certificates were conducted for mortality from multiple sclerosis and non-melanoma skin cancer (as a positive control) to examine associations with residential and occupational exposure to sunlight. Cases were all deaths from multiple sclerosis between 1984 and 1995 in 24 states of the United States. Controls, which were age frequency matched to a series of cases, excluded cancer and certain neurological deaths. The effects of occupational exposure to sunlight were assessed among subjects with usual occupations requiring substantial activity, so as to exclude those whose indoor jobs resulted from disabilities subsequent to the onset of the disease. Multiple logistic regression analyses were applied, with adjustment for age, sex, race, and socioeconomic status. RESULTS: Unlike mortality from skin cancer, mortality from multiple sclerosis was negatively associated with residential exposure to sunlight (odds ratio (OR)=0.53 (multiple sclerosis) and OR=1.24 (skin cancer)). Odds ratios for the highest occupational exposure to sunlight were 0.74 (95% confidence interval (95% CI) 0.61 to 0.89) for mortality from multiple sclerosis, compared with 1.21 (1.09 to 1.34) for mortality from non-melanoma skin cancer. The OR was 0.24 for the combined effect of the highest levels of residential and occupational exposure to sunlight on multiple sclerosis, compared with an OR of 1.38 for skin cancer. CONCLUSIONS: In this exploratory study, mortality from multiple sclerosis, unlike mortality from skin cancer, was negatively associated with both residential and occupational exposure to sunlight.